Observations on attachment sites of the tick Amblyomma geoemydae (Cantor, 1849) on the Endangered Spiny Hill Turtle, Heosemys spinosa (Gray, 1831), in Borneo - Siti N., Baizurah; Reuben S., K. Sharma; Indraneil, Das (Societas Europaea Herpetologica, 2025)
There remains a paucity of published material on ectoparasites (ticks and leeches) infesting turtles in Borneo. The purpose of this study is: i) to record the attachment sites of ticks on the endangered Spiny Hill Turtle (Heosemys spinosa), an understudied species with limited knowledge of its field biology and; ii) to investigate whether ticks prefer specific attachment sites based on life stages. Attachment sites of the tick Amblyomma geoemydae were recorded on a free-ranging population of H. spinosa at Kubah National Park, Sarawak, East Malaysia (north-western Borneo). Ticks were found externally on the turtle’s body, attached to the forelimbs (51%), hindlimbs (28%), head (8%), carapace (10%) and tail (2%). A total of 109 ticks (10 adult males, 27 adult females, 33 nymphs and 39 larvae) were collected from nine wild H. spinosa (five females, four males). Among these, 72 immature ticks (nymphs and larvae) were found attached on the surfaces of limbs, around axillary areas as larvae (forelimbs: 61%; hindlimbs: 47%) or nymphs (forelimbs: 39%; hindlimbs: 53%). Adult stages were only recorded on the tail and carapace (attached firmly to marginal scutes). A Fisher’s Exact Test revealed a significant association between tick life stages (adult, juveniles) and attachment sites. These observations suggest the versatility of the different life stages of A. geoemydae in occupying different attachment sites on the carapace and soft tissues of the nape and limbs.